O lugar como acontecimento nas imagens de Luiz Braga - Farina, Mauricius Martins (2016)
This essay discuss, through pictures of the brazillian photograph Luiz Braga, the presence of a universe incarnated by the poetic from its documentary origin. In an articulated tension between the photograph in its interconnections — the instant of the shot — and the cultural, in its most organic part, the images present themselves in a atmosphere related to the place that they represent, in its origins and identity aspects, setting territories of belonging in its charming orb